Resource footprint of activities as an element of the digital twin of the enterprise - M. Samosudov (E-Management)
The issues of creation of a digital twin of the enterprise for the purposes of optimisation and automation of management have been considered. It has been shown, that the existing variants of digital twins, modeling, or physical objects used in the activity, or individual, as a rule, technological processes are not in the full sense of the digital twin of the enterprise, which can be used to automate management activities and enterprise management. Such digital twins can be used to automate individual operations and processes, but not the enterprise as a whole. At the same time, it has been noted, that there are solutions to simulate the activities of people, processes taking place in the company, accurately record any phenomena and events, using a certain set of phase variables (system parameters). This сircumstance allows us to come close to solving the problem of forming a full-fledged simulation model of the enterprise, simulating the behavior of the company in the market environment, including the occurrence of an incoming resource flow, crisis situations, etc. – a digital twin. As one of the essential aspects of enterprise activity modeling, individual participants of corporate relations, the fixation of resource transformations occurring in the process of activity in the social system – the socalled resource footprint of activity is considered. Any activity, if viewed from a resource perspective, goes through a certain cycle of resource transformations. Moreover, this is manifested at any scale of activity – due to the fractal properties of the activity.Thus, using the developed methods, it is possible to fix resource footprint of activity and thereby definitely to fix the state change of the social system, that allows us to estimate its functional stability, to calculate the consequences of the implementation of management actions before performing them, that is, to calculate the action for control.